Can Sluggish Cognitive Tempo be Distinguished from ADHD Inattention in Very Young Children? Evidence from a Sample of Korean Preschool Children - Lee, SoYean (J Atten Disord, 2016)
OBJECTIVE: This study evaluated whether SCT is separable from attention-deficit/hyperactivity disorder (ADHD) inattention (IN), and uniquely associated with internalizing dimensions, in preschool children in South Korea. METHOD: Mothers of 172 preschool children (ages 4–6 years; 52% girls) rated children’s SCT, ADHD-IN, ADHD-hyperactivity/impulsivity (HI), oppositional defiant disorder (ODD), aggression, emotional reactivity, anxiety/depression, somatic complaints, withdrawal, and sleep problems. RESULTS: Eight of ten SCT symptoms showed convergent and discriminant validity with ADHD-IN. ADHD-IN remained significantly positively associated with ADHD-HI, ODD, and aggressive behavior after controlling for SCT, whereas SCT was no longer positively associated with these externalizing behaviors after controlling for ADHD-IN. Both SCT and ADHD-IN were uniquely associated with greater emotionally reactivity, anxiety/depression, and withdrawal. Only SCT was uniquely associated with somatic complaints and only ADHD-IN was uniquely associated with sleep problems. CONCLUSION: Findings replicate results with children and adolescents, thus expanding evidence for the validity of SCT in early development.